Planting Date by Maturity Group in Kansas: 2016 Season and Three-Year Summary - I. A. Ciampitti; O. Ortez; D. E. Shoup; Eric Adee; J. Kimball; Gretchen Sassenrath; G. Cramer (Kansas Agricultural Experiment Station Research Reports, 2017)
Optimal planting should be timed to capture a favorable environment (e.g., fall rains and cooler temperatures during grain filling). Five field studies were conducted during the 2014 growing season (Manhattan, Topeka, Ottawa, Parsons, and Hutchinson); five in 2015 (Manhattan, Rossville, Ottawa, Parsons, and Hutchinson); and three in 2016 (Manhattan, Topeka, and Ottawa). This study explores the impact of planting date (early-, mid-, and late-planted) on yield for soybean cultivars from a range of maturity groups (early, medium, and late groups). For 2016, the overall main factor impacting yield across sites was planting date, which increased yields with early-planted soybeans. Based on all 13 sites (2014, 2015, and 2016), maximum soybean yield potential decreased by 0.5 bushels per day of delay on planting date when soybean is planted after April 15. Comparable yield penalties have been documented for other main production regions. In summary, weather patterns dictate soybean yields, especially under dryland conditions. There is no guarantee that any certain planting date will always work out the best when it comes to soybean yields in Kansas.
Keywords: soybean; planting date; maturity group